STRATEGI PROMOSI PADA TOSERBA GANDUNG DAN SOPONGIRO SURABAYA - Wardhanie, Ayouvi Poerna; Hananto, Valentinus Roby; Ningsih, Norma (Jurnal Ilmiah Bisnis dan Ekonomi Asia, 2017)
Along with the development of technology, retail business in society is becoming increasingly important. The retail business is initially seen only limited to providers of goods and services only, is now viewed as a business that is more innovative, dynamic, and competitive. This study is intended for retail store owners and employees to train the design drawings and writings using Adobe Photoshop as a tool to increase sales promotion. The results of these community service is the module manufacturing of Adobe Photoshop, as a guide to make the design drawings, manufacturing of job description framework of each business owner and employee, and the outcome of training design drawings using Adobe Photoshop is used in the media campaign such as t-shirts, banners, posters and billboards.